Oliver Twist [videorecording (DVD)] - Lean, David, 1908-1991; Lean, David, 1908-1991; Davies, John Howard, 1939-2011; Newton, Robert, 1905-1956; Guinness, Alec, 1914-2000; Walsh, Kay; Sullivan, Francis L.; Harrison, Kathleen, 1892-1995; Dickens, Charles, 1812-1870 (Criterion collection, 1998)
After escaping from the dreary workhouse where he has spent his childhood, Oliver runs away to London, only to fall in with Artful Dodger, Fagin, and their gang of young thieves. It is only with the revelation of Oliver's true identity that his troubles finally end.